Emerging Stages and Types of Electronic Commerce In the Digital Economy (Eurasian Scientific Herald, 2022)
This article analyzes the role of e-commerce in the digital economy, the development of the trade sector to the level of e-commerce, the increase in the scale of e-commerce, and the factors influencing the development and quality of e-commerce in the digital economy